2010
DOI: 10.1016/s1875-9572(10)60004-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of House Dust Mite-specific Immunotherapy in Asthmatic Children

Abstract: Our study showed that specific immunotherapy with Dp and Df was beneficial for asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
2
26
0
2
Order By: Relevance
“…All these studies demonstrated that the AIT treated group had a significant decline in the medication score compared with the placebo group (54,55,134,234).…”
Section: Asthma Controlmentioning
confidence: 98%
See 4 more Smart Citations
“…All these studies demonstrated that the AIT treated group had a significant decline in the medication score compared with the placebo group (54,55,134,234).…”
Section: Asthma Controlmentioning
confidence: 98%
“…The efficacy of AIT in asthma is measured using symptom scores, medication scores, as well as lung function test (55,134,(233)(234)(235). The symptom and medication scores are frequently used as primary endpoints in AIT trials.…”
Section: Asthma Controlmentioning
confidence: 99%
See 3 more Smart Citations